PENGUATAN KETAHANAN PANGAN KELUARGA PERKOTAAN MELALUI URBAN FARMING SAYURAN ORGANIK DAN PASCAPANENNYA DI PERUMAHAN SAPPHIRE KELURAHAN KARANGWANGKAL BANYUMAS JAWA TENGAH - Prita Sari Dewi; Hadi, Sapto Nugroho; Ferrawati, Kartika (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Urban families play an important role in supporting food security. However, reliance on food supplies from rural areas renders urban areas vulnerable to food insecurity. Urban farming is one strategy for strengthening food security among urban communities. This community service program targeted members of family welfare programs residing in RT 01/RW 06 of the Sapphire Residential Complex, Karangwangkal Village, Banyumas Regency, Central Java, Indonesia. The objectives of the program were to: (1) deliver information on the importance of preparing healthy meals for families to strengthen urban household food security; (2) provide training in organic vegetable cultivation, covering growth-medium preparation, seedling, planting, maintenance, and harvesting; (3) provide postharvest training to process vegetables into value-added food products (e.g., vegetable ice cream); and (4) establish demonstration plots for urban farming of various organic vegetables. The program engaged family welfare program members as active participants in urban organic vegetable farming and postharvest processing through socialization sessions, pretests, hands-on trainings, and field demonstrations. All planned activities were implemented as intended, including socialization and pre-testing, establishment of demonstration plots, training on organic vegetable cultivation, training on making vegetable ice cream, and counseling on the importance of preparing healthy family meals. Pre-and post-test results showed significant improvements in participants’ knowledge and skills. — Keluarga perkotaan memiliki peran penting dalam mendukung ketahanan pangan. Kebergantungan perkotaan terhadap pasokan pangan dari perdesaan membuat wilayah ini rentan ketahanan pangan. Kegiatan urban farming menjadi bagian usaha untuk menguatkan ketahanan pangan masyarakat perkotaan. Kegiatan Pengabdian kepada Masyarakat ini menargetkan mitra kelompok ibu PKK RT 01 RW 06 Perumahan Sapphire Kelurahan Karangwangkal Kabupaten Banyumas Jawa Tengah. Tujuan kegiatan PkM ini adalah (1) memberikan sosialisasi dan penyuluhan terkait pentingnya penyiapan pangan sehat bagi keluarga demi ketahanan pangan masyarakat perkotaan, (2) memberikan pelatihan budidaya sayuran secara organik dari mulai penyiapan media tanam, penyemaian, penanaman, pemeliharaan, sampai pemanenan, dan (3) memberikan pelatihan pascapanen produk sayuran menjadi produk makanan bernilai ekonomi seperti es krim sayur, dan (4) menyiapkan demplot/percontohan urban farming aneka sayuran organik. Metode yang dilakukan, yaitu dengan mengajak berperan aktif kelompok Ibu PKK dalam kegiatan urban farming sayuran organik dan pascapanennya. Berdasarkan hasil yang diperoleh, semua kegiatan dapat dijalankan dengan baik seperti sosilasasi dan pre-test, demplot urban farming sayuran organik, pelatihan budidaya sayuran secara organik, pelatihan pembuatan es krim sayur, dan penyuluhan pentingnya penyiapan pangan sehat bagi keluarga. Terdapat peningkatan pengetahuan dan ketrampilan ibu-ibu PKK berdasarkan hasil post- dan pre-test kegiatan PkM.